PENGARUH KECERDASAN INTELEKTUAL TERHADAP KINERJA GURU DALAM MENGAJAR DI SMAN 5 KEDIRI - Enny Sustiyatik (RJABM (Research Journal of Accounting and Business Management), 2019)
Logically the theacher has manner to improve his performance in teaching students at school.This will affect if the use of intellectual intelligence is used in teaching. The purpose of this study was to determine the effect of intellectual intelligence on teacher performance at SMAN 5 Kediri.The use of analysis in this study is a logistic regression test by taking the results of the final phase likehood ratio test andthen  Wald test and the result of the significant value to get a reference with the logit category do not agree, less agree and agree from the dominant value category strongly agree. The results obtained are significant variables, the variables are  X1, X3, X4, X7, X8, X9, X10, X11, X12, X14 due to use of a 95% confidence level. Then, the variable was tested Wald get the results of the category disagree because the current conditions that are easy to change but are still suitable for research use with the results of the suitability test that has meaning if the Sig. > alpha (p-value > 0.0050) it is that the model used is in accordance with variable data and can be used.